PENGARUH ORIENTASI FASHION, MONEY ATTITUDE, DAN SELFESTEEM TERHADAP PEMBELIAN KOMPULSIF DAN GAYA HIDUP HEDONIS PRODUK SNEAKERS NIKE PADA MAHASISWA FAKULTAS EKONOMI & BISNIS UNIVERSITAS RIAU - Firman, Prabowo; Sri, Restuti; Rendra, Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
Every human being lives by their own views and ideologies.Their demonstrate what they believe by their attitudes and lifestyle that they adopt. One of the more developed ideologies of society is Hedonism.For large communities, Hedonism is defined as extravagant, squandering, and just thinking about earthly happiness which leads to negative behavior. One form of negative behavior from hedonism is Compulsive Buying. Compulsive Buying is an act of persons in the purchasing of goods not on account of their need, but for gratification of their overindulgence, chronic and repeated desires with weak control as a form of negative feelings or to alleviate negative feelings, with adverse consequences. This study aims to identify the profound effects of factors which affecting compulsive buying behavior and hedonism of Sneakers Nike user on the Student of Faculty Economics & Business of Riau University. The primary data was collected with structured questionnaires and interviews as instruments in verifying research results. The research was using 116 students as responders with Non-Probability Sampling techniques. The method used was Explanatory Research with data analysis, classical assumptions, hypothetical test and Path Analysis as lines of data testing and aided by 23rd version of SPSS application in data processing. The result of this study indicate that the variable of Fashion Orientation and Self Esteem affect to Compulsive Buying and Hedonism, both directly and indirectly. And only the variable of Money Attitude has negative influence on Compulsive Buying and Hedonism, both directly and indirectly.Keywords : Fashion Orientation, Money Attitude, Self Esteem, Compulsive Buying Behavior, Hedonism.